The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acsaem.8b00367
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Impurity Gettering Layers in Polysilicon-Based Passivating Contacts for Silicon Solar Cells

Abstract: The formation of certain types of doped polysilicon passivating contacts for silicon solar cells is recently reported to generate very strong impurity gettering effects, revealing an important additional benefit of this passivating contact structure. This work investigates the underlying gettering mechanisms by directly monitoring the impurity redistribution during the contact formation and subsequent processes, via a combination of secondary ion mass spectrometry (SIMS), transmission electron microscopy (TEM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…However, further increase in doping concentration caused the drop in bulk iV OC from 710 to 670 mV. This might be caused by the reappearance of gettered impurities, which is also represented by Liu et al 11 Thus, we concluded that poly-Si is required for contact because SiO x would get destroyed without poly-Si. The poly-Si layer plays the following roles: (1) contact, (2) in-diffusion barrier, and provides (3) eld effect and (4) gettering.…”
Section: Controlling Passivation Qualitysupporting
confidence: 52%
See 2 more Smart Citations
“…However, further increase in doping concentration caused the drop in bulk iV OC from 710 to 670 mV. This might be caused by the reappearance of gettered impurities, which is also represented by Liu et al 11 Thus, we concluded that poly-Si is required for contact because SiO x would get destroyed without poly-Si. The poly-Si layer plays the following roles: (1) contact, (2) in-diffusion barrier, and provides (3) eld effect and (4) gettering.…”
Section: Controlling Passivation Qualitysupporting
confidence: 52%
“…The gettering effect of the poly-Si passivating contact was studied by A. Liu. 10,11 In our research, the gettering effect was conrmed by etching poly-Si/SiO x and the in-diffused region, and repassivating the sample using a 10 nm-thick aluminum oxide layer. We conrmed that by increasing the doping concentration from 8 Â 10 19 cm À3 to 1.8 Â 10 20 cm À3 , the bulk quality improved as iV OC aer etching the poly-Si/c-Si, from 693 to 705 mV.…”
Section: Controlling Passivation Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The driving force of the impurity gettering by B‐doped layers is often a combination of segregation due to precipitation at the surface of the p+ layer, Fermi level effect, and Fe–B pairing . However, for heavily doped layers, the impurity gettering seems to be preferentially realized by the BRL . Segregation due to chemisorption from the B‐Si precipitates formed in the BRL is considered to be one of the possible physical mechanisms involved .…”
Section: Resultsmentioning
confidence: 99%
“…In the first case, pinholes are formed by increasing the annealing temperature above 1000°C in oxide layers above 2 nm [20]. In the second case, the transport of carriers is described by tunneling through a potential energy barrier built by an oxide layer around 1.5 nm thick [22], [30]- [33], implying process temperatures lower than 950°C. It is worth noting that several studies within state-of-the-art complementary metal oxide semiconductor (CMOS) devices [34]- [40] confirm that leakage currents though thin dielectrics are based on tunneling.…”
Section: Introductionmentioning
confidence: 99%